Ableist obstetric violence against women with disabilities: An integrative literature review - Pía Rodríguez-Garrido (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2023)
Women with disabilities face increased precarity throughout their lives, with one of the most affected areas being their sexual and reproductive health. The aim of this study was to identify and analyze the scientific literature on obstetric violence against women with disabilities. The search was conducted from August to October 2022 in five databases: PubMed, Web of Science, Dialnet, SciELO, and Scopus. A total of 194 articles were retrieved, and after applying selection criteria, ten articles were analyzed. Through thematic analysis, the dimension "ableist obstetric violence towards women with disabilities" emerged. Findings suggest that women with disabilities are marginalized during obstetric care, resulting in untimely attention and cascading interventions. At present, there is scarce literature addressing this phenomenon from a rights-based perspective. Urgent measures are needed to train healthcare teams on the provision of care to people with disabilities. Additionally, it is crucial to critically examine the relationship between healthcare personnel and institutions to women with disabilities within the framework of their sexual and reproductive rights.